2009
DOI: 10.3998/ark.5550190.0010.b28
|View full text |Cite
|
Sign up to set email alerts
|

One-pot diastereoselective synthesis of new spiro indenoquinoxaline derivatives containing cyclopropane ring

Abstract: A one-pot procedure was introduced for the synthesis of some new spiro derivatives of indenoquinoxaline containing cyclopropane ring from chalcones. The chalcones 1a-e were reacted with hydrazine hydrate and then in situ with lead(IV) acetate (LTA) and two new diastereomers 2a-e and 3a-e were prepared. The compounds 2a-e diastereoselectively produced in higher yields than 3a-e.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Thus, a series of enantiomerically pure, novel chiral heterocyclic spiroindenoquinoxaline pyrrolizidines (SIQPs) with high yields via a one-pot, three-component 1,3-dipolar cycloaddition reaction under normal conditions using moieties of highly efficient azomethine ylides have been synthesized. For SIQP synthesis at RT, −NO 2 was introduced in IQ, saving 80% resources with new properties and activities contrary to the IQs reported elsewhere. , Introducing the −NO 2 group to IQ, i.e., nitro-indenoquinoxaline (NIQ) using methanol (CH 3 OH) and acetic acid (CH 3 COOH) solvents, the SIQPs showed increased affinity toward green solvents with low activation energy ( E a ), thus opening alternative ways for their applications. Efforts are initiated to conduct a similar reaction in a 10% aq CH 3 OH and CH 3 COOH medium separately for a greener synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a series of enantiomerically pure, novel chiral heterocyclic spiroindenoquinoxaline pyrrolizidines (SIQPs) with high yields via a one-pot, three-component 1,3-dipolar cycloaddition reaction under normal conditions using moieties of highly efficient azomethine ylides have been synthesized. For SIQP synthesis at RT, −NO 2 was introduced in IQ, saving 80% resources with new properties and activities contrary to the IQs reported elsewhere. , Introducing the −NO 2 group to IQ, i.e., nitro-indenoquinoxaline (NIQ) using methanol (CH 3 OH) and acetic acid (CH 3 COOH) solvents, the SIQPs showed increased affinity toward green solvents with low activation energy ( E a ), thus opening alternative ways for their applications. Efforts are initiated to conduct a similar reaction in a 10% aq CH 3 OH and CH 3 COOH medium separately for a greener synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…For SIQP synthesis at RT, −NO 2 was introduced in IQ, saving 80% resources with new properties and activities contrary to the IQs reported elsewhere. 6,7 Introducing the −NO 2 group to IQ, i.e., nitroindenoquinoxaline (NIQ) using methanol (CH 3 OH) and acetic acid (CH 3 COOH) solvents, the SIQPs showed increased affinity toward green solvents with low activation energy (E a ), thus opening alternative ways for their applications. Efforts are initiated to conduct a similar reaction in a 10% aq CH 3 OH and CH 3 COOH medium separately for a greener synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclopropane ring-containing compounds are structural parts of various synthetic and naturally occurring compounds and exhibit anti-viral, anti-tumor, antibiotic and other potent activities. [17][18][19][20] Shaabanzadeh et al 21 have reported the synthesis of two diastereoisomers of a new spiro-indenoquinoxaline system 2 0 -acetyloxy-2 0 -phenylspiro[indeno[1,2-b]quinoxalin-11,1 0 -cyclopropane] 5 and 5 0 in a 3 : 1 ratio from the reaction of chalcones of indeno[1,2-b]quinoxaline 4 with hydrazine hydrate in the presence of solid lead(IV) tetraacetate (LTA) at 85 C (Scheme 2). Chalcones have previously been prepared by the reaction of indenoquinoxalinone 3 with acetophenones in the presence of dimethylamine as a base catalyst in acetic acid and HCl.…”
Section: Synthesis Of Indeno[12-b] Quinoxalinonementioning
confidence: 99%